Exploring Humanistic Layers of Urban Travel: Representation, Imagination, and Speculation. Issue 3 (1st December 2019) - Kim, Jooyoung; Kim, Taehee; Lee, Jinhyoung; Shin, Inseop
Abstract : This think piece approaches urban travel from a mobility humanities perspective, using the example of Seoul, South Korea, a leading metropolis in Asia. The article demonstrates three modes of interpreting urban travel in Seoul: (1) representation by means of mobile video technologies embodying a paradoxical relationship of powers; (2) literary imagination confining a possible mobile community in a restricted region; and (3) philosophical speculation presenting "crossing the Han River" as a spiritual and emotional reproduction of the connection between, and consequential rupture of, heterogeneous territories. The article pays particular attention to the represented, imagined, and speculated dimensions of urban travel, which is understood as a physically practiced and cognitively elaborated production, rather than a predefined movement per se.